Pengaruh Gaya Kepemimpinan, Komitmen Organisasi Dan Kepuasan Kerja Terhadap Kinerja Pegawai Pada KPPBC TMP C Pangkalan Bun Kalimantan Tengah - Ryan Arist; Haryani Haryani (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The purpose of this research is to find out the influence of leadership style, organizational commitment, and job satisfaction on the performance of KPPBC TMP C Pangkalan Bun employees. The population in this study were 60 employees of KPPBC TMP C Pangkalan Bun. This sample was determined using a saturated sampling technique. The number of samples used in this research was 60 employees. This research data analysis tool uses multiple linear regression. The research results show that leadership style has no effect on employee performance. Organizational commitment has a positive effect on employee performance. Job satisfaction has a positive effect on employee performance.